Evaluating the effectiveness of a large-scale professional development programme. Issue 5 (20th October 2017) - Main, Katherine; Pendergast, Donna
Abstract : An evaluation of the effectiveness of a large-scale professional development (PD) programme delivered to 258 schools in Queensland, Australia is presented. Formal evaluations were conducted at two stages during the programme using a tool developed from Desimone's five core features of effective PD. Descriptive statistics of 38 questions and thematic content analysis of open-ended responses reveal that the PD programme was reported to be effective for all five domains evaluated: duration; content focus; active learning; collective participation; and coherence. Recommendations arising from the planning and delivery of the programme include that future PD should be designed and evaluated in line with the framework that considers the evidence-based features of effective PD.